Incidencia de la adicción del internet en el desarrollo académico de las estudiantes del bachillerato del Colegio Dr. Camilo Gallegos Domínguez de la ciudad de Arenillas, periodo lectivo 2012-2013. - Carrión Franco, Rocío Paola (2013)
The research work was to determine the incident diction internet in the academic development of students of high school, for the reason next topic was raised. Incidence of internet addiction in the academic development of students Baccalaureate College Dr. Camilo Gallegos Dominguez city of Arenillas, academic year 2012-2013.